Pharmacokinetics and Safety of Esketamine in Chinese Patients Undergoing Painless Gastroscopy in Comparison with Ketamine: A Randomized, Open-Label Clinical Study - Wang J; Huang J; Yang S; Cui C; Ye L; Wang S; Yang G; Pei Q (Dove Medical Press, 2019)
Jing Wang,1,2,* Jie Huang,1,3,* Shuang Yang,1,3 Chang Cui,1,3 Ling Ye,1,3 Sai-ying Wang,4 Guo-ping Yang,1,3 Qi Pei1,2 1Center for Clinical Pharmacology, The Third Xiangya Hospital, Central South University, Changsha, Hunan 410013, People’s Republic of China; 2Department of Pharmacy, The Third Xiangya Hospital, Central South University, Changsha, Hunan 410013, People’s Republic of China; 3Clinical Trails Center, The Third Xiangya Hospital, Central South University, Changsha, Hunan 410013, People’s Republic of China; 4Department of Anesthesiology, The Third Xiangya Hospital, Central South University, Changsha, Hunan 410013, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guo-ping Yang; Qi PeiThe Third Xiangya Hospital, Central South University, Yinpenling Street, Yuelu District, Changsha, Hunan 410013, People’s Republic of ChinaTel +86 131 7041 9804Fax +86 731 8861 8326Email ygp9880@126.com; peiqi1028@126.comPurpose: To assess the pharmacokinetics and safety of pure S-ketamine (esketamine) in Chinese patients undergoing painless gastroscopy and evaluate the potential advantage of esketamine in clinical treatment compared with racemate ketamine hydrochloride injection.Patients and methods: A randomized, open-label, parallel-controlled, Phase I study was performed with 32 patients undergoing painless gastroscopy. Patients received a single dose of esketamine (0.5 mg/kg) or racemic ketamine (1 mg/kg, esketamine:R-ketamine=1:1), injected in 10 s. Blood samples were collected for pharmacokinetic analysis. The concentrations of esketamine, R-ketamine, S-norketamine, and R-norketamine were measured with a validated liquid chromatography with tandem mass spectrometry (LC-MS/MS) method.Results: After administering a single dose of esketamine and racemate ketamine, the pharmacokinetics parameters of esketamine and S-norketamine are both similar in treatment groups. The clearance of esketamine in two groups was 18.1±3.2 and 18.4±3.4 mL/min•kg, respectively. However, in the ketamine group, esketamine has a larger clearance than R-ketamine (18.4±3.4 mL/min·kg vs 15.8±3.1 mL/min·kg, P<0.001). Further analysis showed that gender did not affect the pharmacokinetics of esketamine and racemate ketamine. Regarding the safety of esketamine and racemate ketamine, no serious adverse events were observed during treatment, and the incidences of adverse events were 75.0% (esketamine) and 87.5% (racemate ketamine). The main adverse reactions were dizziness, agitation, nausea, vomiting, headache, and fatigue. However, compared with racemic ketamine, esketamine offers a shorter recovery time (9 mins vs. 13 mins, P<0.05) and orientation recovery time (11.5 mins vs. 17 mins, P<0.05) after short anesthesia.Conclusion: Esketamine administration as a single dose of 0.5 mg/kg was generally safe and tolerated in patients undergoing painless gastroscopy. In terms of anesthesia, a relatively small dose of esketamine can be used instead of racemate ketamine for routine treatment without consideration of gender differences.Keywords: pharmacokinetics, esketamine, racemate ketamine, anesthesia, Chinese patients